Pengaruh Gaya Kepemimpinan Transformasional Kepala Sekolah Dan Motivasi Kerja Terhadap Kompetensi Guru (Studi Pada Guru Smk Daerah Pinggiran Kabupaten Tulungagung) - Lia Dwi Purwanti; Bayu Cahyoadi (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2021)
This study aims to determine the effect of the principal's transformational leadership style on work motivation; the influence of the principal's transformational leadership style on teacher competence; and the effect of work motivation on teacher competence. The purpose of the study was made because based on facts about teacher competence, because some teachers in SMK in the outskirts of Tulungagung Regency have low competency, such as teachers in making lesson plans less accurate and still having difficulty in implementing the 2013 curriculum.This research method uses quantitative research methods with a population of 230 teachers. The sampling technique uses a random sampling of 200 teachers. Variables consist of the principal's transformational leadership style (X1), work motivation (X2), and teacher competency (X3). Data collection using documents and questionnaires. The data analysis technique used is Structural Equation Modeling (SEM). The results showed that: the transformational leadership style of the principal had a significant positive effect on work motivation shows a probability value of 0,000 below the p value of 0.05; the transformational leadership style of the principal does not have a significant positive effect on teacher competency, indicating a probability value of 0.296 above a p value of 0.05; Work motivation has a significant positive effect on teacher competency showing a probability value of 0,000 below the p value of 0.05. DOI: https://dx.doi.org/10.17977/UM014v14i12020p37